Non-cracked oil in ultra-deep high-temperature reservoirs in the Tarim basin, China. (January 2018) - Zhu, Guangyou; Milkov, Alexei V.; Chen, Feiran; Weng, Na; Zhang, Zhiyao; Yang, Haijun; Liu, Keyu; Zhu, Yongfeng
Abstract: Thermal stability of liquid petroleum in the subsurface is closely linked to reservoir temperature. Most oil accumulations occur at temperatures <120 °C. Oil cracks into gas at temperatures >150–160 °C leading to the dominance of gas condensate and free gas accumulations in ultra-deep high-temperature reservoirs. The recently drilled Fuyuan-1 exploration well (northern Tarim basin) produced high-quality non-cracked single-phase (black) oil from a carbonate reservoir located at maximum depth 7711 m and temperature 172 °C. This is the deepest oil discovery in China to date and among the deepest in the world. The oil density (0.825 g/cm 3 at 20 °C or API gravity 40°), relatively low gas/oil ratio (135 m 3 /m 3 or 758 scf/bbl), low variety and abundance of adamantanes as well as lack of thiaadamantanes and dibenzothiophenes indicate that the oil was expelled from a source rock at moderate thermal maturity and has not been cracked. The molecular and isotopic composition of oil-associated gases are consistent with this interpretation. We suggest that the oil remained uncracked because the residence time at temperatures >150-160°C was relatively short (<5 my based on 1D modeling) and apparently insufficient for cracking. We conclude that there is potential for finding unaltered liquid petroleum in other high-temperature reservoirs with relatively low geothermal gradient and recent burial in the Tarim basin and around the world. Highlights: Evidence of non-cracked oil from high-temperature reservoirs are presented. Oil is preserved due to short residence time at high temperatures. Single-phase unaltered oil can be present in ultra-deep high-temperature reservoirs.